Pengaruh Model Kooperatif Tipe Think Pair Share (TPS) dalam Meningkatkan Keterampilan Bahasa Arab Siswa di MA Wali Songo Sukajadi Lampung Tengah - Latifah, Umi; Yaqin, Muhamaad Ainul; Masuwd, Mowafg (Al Maghazi : Arabic Language in Higher Education, 2024)
This study aims to evaluate the effectiveness of the Cooperative Learning Model of Think Pair Share (TPS) in improving the Arabic language skills of tenth-grade students at MA Wali Songo Sukajadi. The research method used a One-Group Pretest-Posttest Design with a sample of 30 tenth-grade students at MA Wali Songo. Data were collected through written tests before (pre-test) and after (post-test) the implementation of TPS. The results of the study showed a significant improvement in the Arabic language skills of students after the implementation of TPS, as indicated by an N-Gen value of 18.5. These findings demonstrate that TPS is effective in enhancing the understanding and mastery of the Arabic language by students. In conclusion, the implementation of the Cooperative Learning Model of Think Pair Share (TPS) can be an effective solution in improving the Arabic language skills of students at MA Wali Songo Sukajadi. This learning model encourages active student participation, facilitates collaborative learning, and has a positive impact on their understanding of religion.